Selling the Suburbs to Montrealers: Advertising Discourse and Strategies, 1950–1970 - Bérubé, Harold (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2024)
This article addresses the way mass suburbanization was marketed to Montrealers in the 1950s and 1960s. Advertisements for newly built, single-family homes in anglophone and francophone newspapers evidence the evolution of marketing strategies and the construction of the suburban ideal that underpinned them, shedding light on what constituted the typical publicity for this period as well as the changing discourses and strategies used and their convergence for the two linguistic groups (at least, as far as content is concerned).